Burmusculidae, a new and basal family of pompiloid wasps from the Cretaceous of Eurasia (Hymenoptera: Pompiloidea). (November 2018) - Zhang, Qi; Rasnitsyn, Alexandr P.; Zhang, Haichun
Abstract: A group of aculeate wasps from mid-Cretaceous Burmese amber is described as Burmusculus Zhang and Rasnitsyn, gen. nov. in Burmusculidae Zhang and Rasnitsyn, fam. nov. The type genus Burmusculus contains three new species: Burmusculus nuwae Zhang and Rasnitsyn, sp. nov., Burmusculus fuxii Zhang and Rasnitsyn, sp. nov., and Burmusculus shennongii Zhang and Rasnitsyn, sp. nov. It does not fit any described families and therefore is referable to a new family. The family displays some features in common with the living family Pompilidae but can be easily distinguished from Pompilidae in having the mesopleuron lacking an oblique suture. Hence it is assigned to the superfamily Pompiloidea (monotypical as yet in our understanding) as the second member.